A new particle mounting method for surface analysis. (8th September 2021) - Dundas, Adam A.; Kern, Stefanie; Cuzzucoli Crucitti, Valentina; Scurr, David J.; Wildman, Ricky; Irvine, Derek J.; Alexander, Morgan R.
Abstract : The chemical analysis of microparticles is challenging due to the need to mount the particles on a substrate for analysis; double‐sided adhesive tape is often used (sometimes conductive), however that is usually coated with poly (dimethyl siloxane) (PDMS) that is often used as a release agent. PDMS is a common surface contamination that can mask surface chemistries and hinder material performance where it is dependent on this contaminated interface. It is known that PDMS contains a very mobile oligomeric fraction that readily diffuses across surfaces resulting in the contamination of mounted particulate samples before and during surface chemistry analysis. This makes it impossible to determine whether the PDMS has arisen from the analysis procedure or from the sample itself. A new sample preparation method is proposed where polymer microparticles are mounted on a poly (hydroxyethyl methacrylate) (pHEMA) polymer solution, which we compare with particles that have been mounted on adhesive discs using time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) and 3D OrbiSIMS analysis. Particles mounted on the pHEMA substrate results in a reduction of PDMS signal by 99.8% compared with microparticles mounted on adhesive discs. This illustrates how a simple, quick and inexpensive polymer solution can be used to adhere particles for analysis by ToF‐SIMS, or other surface chemical analysis techniques such as X‐ray photoelectron spectroscopy (XPS), without introduction of large amounts of silicone contaminant.